Understanding NK cell biology for harnessing NK cell therapies: targeting cancer and beyond - Shin, Eunju; Bak, Seong Ho; Park, Taeho; Kim, Jin Woo; Yoon, Suk-Ran; Jung, Haiyoung; Noh, Ji-Yoon (Frontiers in Immunology, 2023)
The use of gene-engineered immune cell therapies has partially transformed cancer treatment, exemplified by chimeric antigen receptor (CAR)-T cells in certain hematologic malignancies. However, there are still several limitations that need to be addressed to target more cancers. Natural killer (NK) cells are a type of innate immune cells and represent unique biology in cancer immune surveillance. In particular, NK cells obtained from a heathy donor can provide a source for gene-engineered immune cell therapy. Therefore, NK-based therapies, including NK cell, CAR-NK cell, and antibodies that induce antibody-dependent cellular cytotoxicity of NK cells have emerged. Together with the recent advances in genetic engineering and cell biology techniques, NK cell-based therapies become promising approaches for a wide range of cancers, viral infections, and senescence. This review provides a brief overview of NK cells’ characteristics and summarizes the diseases that could benefit from NK-based therapies. In addition, we discuss recent preclinical and clinical investigations on the use of adoptive NK cell transfer and agents that can modulate NK cell activity.